Shariah monitoring, agency cost and fund performance in Malaysian mutual funds - Sofi, Mohd Fikri; Yahya, M. H. (Emerald Publishing, 2020)
Purpose This paper aims to examine the effect of Shariah Advisory Panel (SAP) on both the level of agency cost and fund performance against conventional corporate governance, within corporate and Shariah governance settings, between Shariah and conventional mutual fund (CMF), in an emerging economy of Malaysia during the period 2008-2015.